2022
DOI: 10.3390/jof8101054
|View full text |Cite
|
Sign up to set email alerts
|

The Cynomolgus Macaque Intestinal Mycobiome Is Dominated by the Kazachstania Genus and K. pintolopesii Species

Abstract: The cynomolgus macaque, Macaca fascicularis, is a non-human primate (NHP) widely used in biomedical research as its genetics, immunology and physiology are similar to those of humans. They may also be a useful model of the intestinal microbiome as their prokaryome resembles that of humans. However, beyond the prokaryome relatively little is known about other constituents of the macaque intestinal microbiome including the mycobiome. Here, we conducted a region-by-region taxonomic survey of the cynomolgus intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…We also found that Kazachstania represented the main genus in both the small and large intestines of cynomolgus monkeys, which is in accordance with previously reported results (Fig. S4) ( 30 ). However, in human beings, Candida was identified as the dominated mucosa-associated genus in the large intestine, while Kazachstania was scarcely detected ( 31 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also found that Kazachstania represented the main genus in both the small and large intestines of cynomolgus monkeys, which is in accordance with previously reported results (Fig. S4) ( 30 ). However, in human beings, Candida was identified as the dominated mucosa-associated genus in the large intestine, while Kazachstania was scarcely detected ( 31 ).…”
Section: Discussionsupporting
confidence: 93%
“…In cynomolgus monkeys, the gut bacteria from different sites of the large intestine (caecum and ascending, transverse, and descending colons) had been studied; however, the bacterial community of the small intestine was uncharacterized ( 29 ). As for the fungal microbiome, a region-by-region taxonomic survey of intestinal fungi revealed that the Kazachstania genus and K. pintolopesii species dominated in both the small and large intestines of cynomolgus monkeys ( 30 ). While the composition of intestinal bacteria and fungi was studied along the GI tract of cynomolgus monkeys, the gut biogeography of bacteria and fungi has rarely been studied simultaneously, and their site-specific interactions have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the discordance of fungal abundance from the samples of feces alone versus feces with intestinal walls due to fungal adherence to the intestinal mucosa is possible. While C. albicans is common in the human gut [62][63][64] and C. tropicalis is associated with IBD in patients [61], the isolated K. pintolopesii, the common fungi in laboratory mice [57,65] might be associated with mouse sepsis severity. As macrophages play a crucial role in the maintenance of intestinal homeostasis, especially gut fungi [22], the fungal overgrowth in the condition without macrophages is not surprising.…”
Section: Macrophage Depletion Facilitated the Growth Of Gut Fungimentioning
confidence: 99%
“…During periods of weakened host immunity or prolonged antibiotic treatment, pathogenic organisms have the potential to cause persistent infections on the surface or within mucosal tissues, as well as life-threatening systemic diseases .…”
Section: Introductionmentioning
confidence: 99%